The first evidence of biological activity for free Hypusine, an enigmatic amino acid discovered in the '70s - Tamborlin, Leticia [UNESP]; Pereira, Karina Danielle; Guimarães, Dimitrius Santiago Passos Simões Fróes; Silveira, Leonardo Reis; Luchessi, Augusto Ducati [UNESP] (Springer Nature, 2023)
Hypusine amino acid [N ε-(4-amino-2-hydroxybutyl)-lysine] was first isolated in 1971 from bovine brain extracts. Hypusine originates from a post-translational modification at the eukaryotic translation initiation factor 5A (eIF5A), a protein produced by archaebacteria and eukaryotes. The eIF5A protein is the only one described containing the hypusine residue, which is essential for its activity. Hypusine as a free amino acid is a consequence of proteolytic degradation of eIF5A. Herein, we showed, for the first time, evidence of biological activity for the free hypusine. C6 rat glioma cells were treated with hypusine, and different cellular parameters were evaluated. Hypusine treatment significantly reduced C6 cell proliferation and potently suppressed their clonogenic capacity without leading to apoptosis. Hypusine also decreased the Eif5A transcript content and the global protein synthesis profile that may occur due to negative feedback in response to high hypusine concentration, controlling the content of newly synthesized eIF5A, which can affect the translation process. Besides, hypusine treatment also altered cellular metabolism by changing the pathways for energy production, reducing cellular respiration coupled with oxidative phosphorylation, and increasing the anaerobic metabolism. These observed results and the relationship between eIF5A and tumor processes led us to test the combination of hypusine with the chemotherapeutic drug temozolomide. Combining temozolomide with hypusine reduced the MTT conversion to the same levels as those observed using double temozolomide dosage alone, demonstrating a synergetic action between the compounds. Thus, since 1971, this is the first study showing evidence of biological activity for hypusine not associated with being an essential component of the eiF5A protein. Finding out the molecular targets of hypusine are the following efforts to completely characterize its biological activity.
Keywords: Cell proliferation; eIF5A; Hypusine; Oxidative metabolism; Post-translational modification; Protein synthesis